Application Of Vortex Induced Vibration Energy Generation Technologies To The Offshore Oil And Gas Platform: The Feasibility Study - T. Yui Khing; M. A. Zahari; S. S. Dol (Zenodo, 2015)
Ocean current is always available around the surrounding of SHELL Sabah Water Platform and data are collected every 10 minutes, 24 hours a day, for a period of 365 days. Due to low current speed, conventional hydrokinetic power generation is not feasible, thus leading to the study of low current enabled vortex induced vibration power generation application. In this case, the design of a vortex induced vibration application is studied to obtain an optimum design for the VIV oscillator. Power output is then determined to study the feasibility of the VIV application in low current condition. : {"references": ["J. Rosebro, Fossil-Fuel Platform Runs on Renewable Energy, 2006.\nhttp://www.greencarcongress.com/2006/04/fossilfuel_plat.html", "E. Goffman, Why Not the Sun? Advantages of and Problems with Solar\nEnergy, Journal of ProQuest Discovery Guides, 2008.", "R. C. Sharma, and N. Sharma, Energy from Ocean and Scope of its\nUtilization in India, Journal of Environmental Engineering and\nManagement, Vol. 4, pp.397-404, 2013.", "Commission of the European Commission, DGXII, Wave Energy\nProject Result: The exploitation of Tidal Marine Currents, Report\nEUR16683EN, ISSN 1018-5593, 1996.", "T. Ball, K. Thomas, S. Shubham, W. Ethan, Maximizing Vortex Induce\nVibrations Through Geometry Variation, Major Qualifying Project: 1-\n89. 2012.", "M. M. Bernitsas, K. Raghavan, Y. Ben-Simon, and E. M. Garcia,\nVIVACE (Vortex Induced Vibration Aquatic Clean Energy): A New\nConcept in Generation of Clean and Renewable Energy from Fluid\nFlow, Journal of Offshore Mechanics and Arctic Engineering, 2006.", "A. Techet, Vortex Induced Vibration. MIT OpenCourseWare,\nMassachusetts Institute of Technology, United States, 2005.", "P. Bassani, E. Gariboldi and A. Tuissi, Calorimetric Analysis of AM60\nMagnesium Alloy. Journal of Thermal Analysis and Calorimetry, Vol.\n80, pp. 739-747, 2005.", "A. Hall-Stinson, C. Lehrman, and E. Tripp, Energy Generation from\nVortex Induced Vibration, Thesis (B.S.), Worcester Polytechnic\nInstitute, United States, 2011.\n[10] M.A. Zahari and S.S. Dol, Application of Vortex Induced Vibration\nEnergy Generation Technologies to the Offshore Oil and Gas\nPlatform: The Preliminary Study, International Journal of\nMechanical, Aerospace, Industrial and Mechatronics Engineering,\n8(7), pp. 1313-1316, 2014.\n[11] M.A. Zahari, S.S Dol, Alternative Energy using Vortex-induced\nVibration from Turbulent Flows: Theoretical and Analytical Analysis,\n5th Brunei International Conference on Engineering and Technology,\nIEEE Xplore Digital Library, 2014.\n[12] M.A. Zahari, S.S Dol, Effects of Different Sizes of Cylinder Diameter\non Vortex-Induced-Vibration for Energy Generation, Journal of Applied\nSciences, 15(5), pp. 783-791, 2015."]}